Acomparative study of vowels in the Acehnese language spoken in Kedah, Malaysia and Aceh, Indonesia / Yunisrina Qismullah Yusuf - Yusuf, Yunisrina Qismullah (2013)

(untitled)
Acehnese is still spoken in Kampung Aceh, Kedah, Malaysia (hereafter, KpA), by Acehnese descents who settled in the area in the late 18th century. Today, they comprise the second to the sixth generations. This study aims to describe oral Acehnese vowels to provide more systematic description of these vowels produced by Acehnese speakers in KpA and as a comparison to Acehnese speakers in Aceh, Indonesia (hereafter, Ach) at the present time. The vowels are based on Asyik’s (1987) description of Acehnese vowels that comprise ten monophthongs: front vowels /i/, /e/, /ɛ/, central vowels /ɯ/, /ǝ/, /ʌ/, /a/, and back vowels /u/, /o/, /ɔ/, and 12 diphthongs divided into centering diphthongs (/iə/, /ɯə/, /uə/, /ɛə/, /ʌə/, /ↄə/) and rising diphthongs (/ui/, /əi/, /oi/, /ʌi/, /ↄi/, /ai/). The data were collected in two speaking contexts: vowels in target words based on a wordlist (hereafter, WE) and target vowels in words selected from interviews (hereafter, INT). The findings from WE and INT indicated that most of the monophthongs vowels by Ach language consultants were generally maintained by KpA language consultants. The sound /ʌ/ was found not to be produced by KpA language consultants, while /ǝ/ was realized closer to [ɵ], and a new sound [ɑ] detected in INT was starting to emerge in their Acehnese. As for the diphthongs, /iə/, /ɯə/, /uə/, /ɛə/, /ui/, /əi/, /ʌi/ /oi/ /ↄi/ and /ai/ were maintained by Ach language consultants, however, /ʌə/ and /ɔə/ were moving towards the back of the vowel space, suggesting [ʌu] and [ɔu] from both contexts. For KpA language consultants, /iә/ and /ɛә/ were realized as monophthongs of [i] and [ɛ]from both WE and INT. From WE, these consultants realized /ɯə/ closer to [ɯɨ], and /uə/ closer to /uɯ/. However, from INT, these diphthongs were realized as monophthongs [ɯ] and [u]. The diphthong /ɔə/ was closer to [ɔo] in WE, but maintained in INT. All instances of /ǝi/ were realized as [oi] from both contexts, /ʌi/ was realized as [ɔe], and /ɔi/ was realized as [oe]. Therefore, the diphthongs maintained were /ɔə/, /ai/, /oi/ and /ui/. An apparent change was seen with the centering diphthongs being produced differently by both sets of speakers. The absence of most of these diphthongs in the Acehnese variety in KpA may be due to the fact that they are not present in the Standard Malay (hereafter, SM) and Kedah dialect (hereafter, KD). This preliminary study has identified some changes that are occurring in the production of the vowels, especially in the variety of Acehnese in KpA. Additional analysis of SM and KD vowels revealed that the maintenance of most monophthongs by KpA language consultants could be due to the shared qualities of these vowels with SM and KD vowels, such as /i/, /e/, /a/ and /o/. The sounds /ɛ/ and /ɔ/ were similarly produced with KD vowels. The sound /u/ was similar to the Acehnese variety in Ach, but produced more fronted compared to SM and KD /u/. KpA language consultants also produced /ai/ and /oi/ similarly to SM and KD, and /ui/ similarly to KD. The motives for KpA language consultants’ sound change and maintenance are seen from their attitudes towards Acehnese language use, identity and efforts to revitalize their mother tongue. From the KpA language consultants’ sense of self, they do not just consider themselves as just Acehnese, but as Acehnese Malaysian as well. Their perception of this identity can be recognized from their variety where some sounds are produced differently from the Acehnese variety in Ach